A mammalian cell line deficient in activity of the DNA repair enzyme 5-hydroxymethyluracil-DNA glycosylase is resistant to the toxic effects of the thymidine analog 5-hydroxymethyl-2'-deoxyuridine. - Boorstein, R J (1992)
We isolated a mutant mammalian cell line lacking activity for the DNA repair enzyme 5-hydroxymethyluracil-DNA glycosylase (HmUra-DNA glycosylase). The mutant was isolated through its resistance to the thymidine analog 5-hydroxymethyl-2'-deoxyuridine (HmdUrd). The mutant incorporates HmdUrd into DNA to the same extent as the parent line but, lacking the repair enzyme, does not remove it. The phenotype of the mutant demonstrates that the toxicity of HmdUrd does not result from substitution of thymine in DNA by HmUra but rather from the removal via base excision of large numbers of HmUra residues in DNA. This finding elucidates a novel mechanism of toxicity for a xenobiotic nucleoside. Furthermore, the isolation of this line supports our hypothesis that the enzymatic repairability of HmUra derives not from its formation opposite adenine via the oxidation of thymine, but rather from its formation opposite guanine as a product of the oxidation and subsequent deamination of 5-methylcytosine.